Knowledge and practices towards breast self examination (BSE) among female nursing student in UNIMAS - Wan Suliana, binti Wan Sulong (Faculty of Medicine & Health Sciences, 2008)
The objectives of this study are to assess the knowledge about breast cancer and breast self examination (BSE), to assess the practices towards breast self examination (BSE) among females UNIMAS student and to identify the source of information about breast cancer and BSE among them